An empirical research on factors affecting customer satisfaction towards fintech products and services in Sungai Petani, Kedah / Barathy Doraisamy ... [et al.] - Doraisamy, Barathy; Appannan, Santhi; M Varatharajoo, Parteeban; Shanmugam, Jaya Kumar; Woo, Hooi Kuan (UiTM Cawangan Negeri Sembilan, 2022)
Since financial institutions have provided almost similar products and services, thus financial firms have been highly competitive in the industry. The results of this competition are based on service quality. Apart from that, the development of technology has caused Fintech products and services to be introduced in Malaysia. This research aims to investigate customer experiences with Fintech products and services. This study also identifies sources of customer satisfaction and dissatisfaction associated with the several factors that impact the use of Fintech products and services in Sungai Petani, Kedah. The main factors of this research are security, convenience, and service quality. Besides that, the result of this study was derived from 200 respondents who are young adults aged between 20 and 39 in Sungai Petani through the online questionnaire survey. Lastly, the study indicated that all of these three independent variables: security, convenience, and service quality have affected customer satisfaction with Fintech.